FREQUENCY OF HYPERURICEMIA IN PATIENTS OF ACUTE ISCHEMIC STROKE - Iqbal, Qaisar; Ahmad, Sarfaraz; Lashari, Naveed; Khan, Muhammad Arif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of hyperuricemia in acute ischemic stroke. Study Design: Cross sectional study. Place and Duration of Study: Medical Unit, Pakistan Air Forces Hospital, Mushaf Sargodha, from Aug 2015 to Jan 2016. Methodology: A total of 125 patients were included in this study that fulfils the inclusion criteria, ischemic stroke on CT scan brain plain (hypo dense area) presented to hospital within 24 hours. Patients with transient ischemic attack (TIA), subarachnoid hemorrhage (SAH), intracerebral hemorrhage (ICH), space occupying lesion (SOL) on neuroimaging (CT scan) and with diagnosed Autoimmune or connective tissue disorders were excluded. Acute ischemic stroke was confirmed by neuroimaging (CT scan brain non contrast) reported by consultant Radiologist (FCPS Radiology) and uric acid level was measured within hospital lab with photometry using the diagnostic kit for quantification of uric acid prepared by (Pars Azmoon Company) and was verified by consultant pathologist. All information and reports were collected on proforma. Results: Age range in this study was from 30-90 years with mean age 60.832 ± 12.01 years and mean uric acid level was 5.773 ± 1.95 mg/dl. Majority of the patients were male (86.4%). Hyperuricemia was seen in 40 (32%) patients. Conclusion: Prevalence of hyperuricemia in patients with acute stroke is significantly higher than normal population.